Characterization and identification of novel biofilm forming antigens of Staphylococcus aureus of human origin - Waryah, Charlene Babra (Curtin University, 2015)
Treatment and prevention of Staphylococcus aureus-associated infections remains a major challenge owing to its versatility to develop persistent antibiotic resistance and produce a wide range of virulence factors including biofilm formation. Other than identifying the most significant virulence factors potentially contributing to biofilm formation, a novel biofilm-associated antigen was identified and characterized in vitro and in vivo. Potential strategies for enhancing efficacy of antibiotics against S. aureus-associated infections were also evaluated provoking recommendations.